2008
DOI: 10.4162/nrp.2008.2.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Soy food intake behavior by socio-demographic characteristics of Korean housewives

Abstract: In this study, the soy food intake behaviors including perception and intake frequency of soybean foods by sociodemographic variables were analyzed in housewives. The perception of housewives for soy foods showed that soybean paste, soybean curd, and Dambuk were high in the descending order for nutritional quality and health promotion effect, and soybean paste received the highest score in taste and flavor. Soybean sprouts received the highest evaluation score in the economic aspect. In the aspect of safe food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Previous studies have suggested that socio-economic status may influence soya consumption patterns ( 38 – 40 ) . The present study found that individuals with a higher level of education were more likely to consume soya, consistent with previous research which has shown that the nutrition and health perceptions of soya foods increase with education level ( 41 ) and knowledge of soya as a functional food ( 42 ) . Similarly, lack of knowledge (preparation techniques and associated health benefits) has been cited as a hindrance to soya consumption ( 43 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that socio-economic status may influence soya consumption patterns ( 38 – 40 ) . The present study found that individuals with a higher level of education were more likely to consume soya, consistent with previous research which has shown that the nutrition and health perceptions of soya foods increase with education level ( 41 ) and knowledge of soya as a functional food ( 42 ) . Similarly, lack of knowledge (preparation techniques and associated health benefits) has been cited as a hindrance to soya consumption ( 43 ) .…”
Section: Discussionsupporting
confidence: 92%
“…The low intake of soy products in this study and other studies in the U.S. is in contrast to higher soy intake in other countries. For instance, a study of soy foods behavior in Korean housewives demonstrated a high intake in most participants of soy foods including soybean curd, soybean paste, Dambuk, soybean sprouts, and soy milk [ 25 ].…”
Section: Discussionmentioning
confidence: 99%